Antecedentsof Online Shopping Attractiveness: The Youngster Perspective (Global Journal of Management and Business Research, 2016)
With growing digitalization and enhancement of IT infrastructure, the youngsters are utilizing the power of internet to buy things online. As the acceptance of online shopping is rising among Indian consumers, the competition is also increasing in E-Commerce space. As many ecommerce websites are in the field, they all are studying the attributes which influence's customers for online shopping. This paper highlights the attributes which leads to online shopping attractiveness in young generation in India. The review of literature identified sixteen important attributes which can be converged into the following four main dimensions that can be named as determinants of online shopping attractiveness: (a) Ease of Transaction (b) Website Image (c) Product Information (d) Website Security. This study is relevant to academician, researchers and industry people who works in the field of E-Commerce.
Keywords: online; shopping; attribute; website; digitalization